Preparing Police Recruits of the Future: An Educational Needs Assessment - Huey, Laura (2017)
Given increasing demand for post-secondary education (PSE) within Ontario’s police applicant pools, coupled with rising costs in post-secondary education, it is of critical importance we ensure the content and quality of PSE programs marketed to students as appropriate for a policing career, does, indeed, match the needs of potential employers. This study examines this issue by drawing on the results of a mixed-methodological approach, combining qualitative interviews of police recruiters and senior officers with an environmental scan of relevant college and university programs. Our findings indicate there are both strengths and weaknesses in the delivery of PSE when it comes to meeting the hiring needs of Ontario’s police agencies. Based on these findings, we provide a series of recommendations to help fill identified delivery gaps